Women Directors And Audit Fees: The Effect Of Company Performance In Indonesian Publicly Listed Companies - Sandy Kuswara; Dimas Luhung Prakoso (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to determine the role of female board directors in influencing audit fees. Furthermore, it also examines the effect of company performance on the influence of female board directors on audit fees. To examine the problem, this study uses upper-echelon theory as a theoretical basis. The sample used in the study was 23 publicly listed mining companies in Indonesia for the 2020-2024 period, comprising both state-owned and private companies, with 115 years of observation data using a purposive sampling method. The research method employed quantitative methods using panel data regression. The research data used were secondary data derived from the companies' annual reports. The results showed that the greater the composition of female directors in a company, a significant positive effect on audit fees (coef = 0.58707; p = 0.078; R2 =0.203). Meanwhile, company performance as a moderating variable had no effect on this relationship (coef = -4.82214; p = 0.340; R2 =0.230). The results of this study can provide input for both state-owned and private companies, suggesting that women are more conservative and cautious in running their companies